Circulating TNF-Alpha and IL-6 Concentrations and TNF-Alpha -308 G > A Polymorphism in Children with Premature Adrenarche - Utriainen, Pauliina; Jääskeläinen, Jarmo; Gröhn, Oskari; Kuusisto, Johanna; Pulkki, Kari; Voutilainen, Raimo (Frontiers in Endocrinology, 2010)
Premature adrenarche (PA), the early rise in adrenal androgen production leading to prepubertal signs of androgen action, has been connected with adverse metabolic features. The metabolic syndrome is characterized by low grade inflammation which in turn is associated with increases in circulating proinflammatory cytokines, like tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). We tested the hypothesis that serum concentrations of TNF-α and IL-6 are increased in PA by studing 73 children with PA and 98 age- and gender-matched controls. Serum TNF-α and IL-6 concentrations were measured using a multiplex bead array. The subjects were genotyped for the TNF-α gene -308 G>A polymorphism (known to affect TNF-α gene transcription), and genotype-phenotype associations were studied. The mean serum TNF-α concentration was higher in the PA than control children (20.4 vs. 18.4 pg/ml, P=0.048), whereas there was no significant difference in the mean serum IL-6 concentrations between the study groups. The difference in TNF-α was not explained by excess body weight in the PA subjects as the difference remained significant after BMI-adjustment (P=0.038). In the PA group, TNF-α concentration was not associated with metabolic-endocrine features, but high IL-6 was associated with lower birth weight. There was no difference in the genotype distribution of the TNF-α gene -308 G>A polymorphism between the PA and control groups. In conclusion, PA was associated with increased serum TNF-α concentrations which, unexpectedly, were not connected with BMI or insulin resistance. The TNF-α gene -308 G>A polymorphism does not seem to be associated with the development of PA.